Exploring Student Technology and Engineering Literacy in Science Learning: an Overview of the Initial Study - Defrizal Hamka; Riandi Riandi; Irma Rahma Suwarma; Sjaeful Anwar (Jurnal Penelitian Pendidikan IPA, 2024)
Technological and engineering literacy is a capability that must be imparted to students in order to be able to compete globally and be able to solve 21st century problems. This study aims to describe aspects of technological and technical literacy of junior high school students. This type of research is descriptive quantitative analysis. Data were obtained from technological and technical literacy test instruments. The test instrument is adopted from tests issued by NAEP. Data were analyzed quantitatively. The research results show that 69.2% in the complete category, 15.4% in the Partial category and incomplete in the Understanding of Technology Principles aspect. The aspect of Developing Solutions and Achieving Goals as many as 54.8% of students fall into the complete category, 19.2% in the Satisfactory category, 15.4% the Essential category, 7.7% the Partial category, and 26.9% incomplete category. Meanwhile, the Communication and Collaboration aspect, 65.4% were in the complete category, and 34.6% were in the incomplete category. three types of assessment targets in the three main TEL assessment areas, with the most complete category being Gather and Organize data and information, followed by Identification of examples of systems or processes and Representation of alternative analysis and solutions. Science learning involving real experiences and design and engineering processes related to technological principles will make students technologically and engineering literate and can improve students' critical thinking and problem solving abilities.